Protection pattern and driving mechanism of typical marine ecosystems: a case study of China-ASEAN countries - Chen, Fenggui; Cui, Zhiyi; Wu, Jianwei; Jiang, Yuhuan; Cai, Feng (Frontiers in Marine Science, 2024)
The protection pattern of typical marine ecosystems is an overall summary of the regional marine ecosystem protection, indicating the protection status of typical marine ecosystems. The coastal waters of China and ASEAN countries have a highly diverse range of ecosystem types, including mangroves, coral reefs, and seagrass beds. The need to protect these ecosystems is urgent, but establishing marine protected areas often involves conflicts with stakeholders highly dependent on these ecosystems. By constructing an analysis model of the protection pattern and driving mechanisms of typical marine ecosystems, with a focus on the China-ASEAN region, this study aimed to analyze the characteristics of typical marine ecosystems protection patterns in China-ASEAN, evaluate the current protection status of these ecosystems, discuss the driving factors, and derive a regression function to clarify the quantitative relationship between the protection pattern and driving factors of typical marine ecosystems in the China-ASEAN region. The results indicate that there are four main driving factors influencing the protection pattern of typical marine ecosystems in China-ASEAN countries. The most significant driving factor is the Natural Geographic and Resource Factor, followed by Urbanization, Industrial Structure, and Population Size and GDP Factor.Among these, the Natural Geographic and Resource Factor and the Industrial Structure Factor have a positive impact, while the others have a negative impact. In the future, it is crucial to fully consider the diversity and distribution of marine ecosystems to promote joint efforts among China-ASEAN countries in protecting marine ecosystems through international cooperation.